Global Innovation Trends for Plant-Based Vaccines Production: A Patent Analysis - Dario G. Frisio; Vera Ventura (Plants, 2021)
The use of plants as biofactories for the production of medical products and vaccines has a long history, but the recent COVID-19 pandemic has caused this set of technologies, for their potential to contribute to the development of innovative solutions for tackling pandemic spread worldwide, to rise in prominence. The purpose of this paper is to analyze the global innovation scenario of plant-based vaccine production. Methods: Patent search using a specific set of technical classification codes and keywords was performed using the Questel-Orbit database, with a final output of 180 patent families, corresponding to 1397 single patents. Results: Plant-based vaccines production is an innovation sector with positive development especially in the last five-year period (30% growth). Fifty percent of the patents were registered in the United States, standing out as the most attractive patent system worldwide. The inventive activity was led by private firms owning the 49% of the patent families, and the key-players group includes the companies that successfully developed plant-based COVID-19 vaccine candidates, indicating a strong connection between the expertise in innovation production and the capacity to adapt inventions to the current pandemic vaccine demand. Virus-like particles technology has increased in importance over the past few years. Conclusion: Patent data confirm their relevant role as indicators of innovation and technological evolution. Plant-based vaccines are expected to acquire an increasing role over the next few years as the current pandemic acts as an innovation catalyst.